170k views
4 votes
If x+3 over 3 = y+2 over 2 then x over 3=

If x+3 over 3 = y+2 over 2 then x over 3=-example-1
User Zuabi
by
5.7k points

1 Answer

4 votes

Given:

The expression


(x+3)/(3)=(y+2)/(2)

Find-:

The value of


(x)/(3)

Explanation-:

The value is


\begin{gathered} (x+3)/(3)=(y+2)/(2) \\ \\ (x)/(3)+(3)/(3)=(y)/(2)+(2)/(2) \end{gathered}

The value of x/3 is


\begin{gathered} (x)/(3)+(3)/(3)=(y)/(2)+(2)/(2) \\ \\ (x)/(3)+1=(y)/(2)+1 \\ \\ (x)/(3)=(y)/(2)+1-1 \\ \\ (x)/(3)=(y)/(2) \end{gathered}

The value is y/2

User JonTargaryen
by
5.6k points